Hepatic perfusion as a new predictor of prognosis and mortality in critical care patients with acute-on-chronic liver failure - Vogg, Johannes; Maier-Stocker, Constantin; Munker, Stefan; Mehrl, Alexander; Schlosser, Sophie; Tews, Hauke Christian; Gülow, Karsten; Müller, Martina; Schmid, Stephan (Frontiers in Medicine, 2022)
Background & Aims: Liver diseases are frequent causes of morbidity and mortality worldwide. Liver diseases can lead to cirrhosis, with the risk of acute-on-chronic liver failure (ACLF). We investigated hepatic hemodynamics via serial Doppler ultrasonography to determine the predictive value of changes in hepatic perfusion for the outcome in patients with severe liver diseases compared to established prognostic models such as the MELD or CLIF-C ACLF score. Methods: In this prospective cohort study, hepatic perfusion was quantified at baseline before the initiation of treatment and every third day by means of serial measurements of the hepatic artery resistance index (HARI) and the maximum portal vein velocity (PVv) using Doppler ultrasonography in 50 consecutive patients with severe liver diseases admitted to a medical intensive care unit. The recorded hemodynamic parameters were compared to the MELD score, and the CLIF-C ACLF score. Results: The changes (delta) obtained by serial measurements of the MELD score, HARI, and PVv were analyzed through scatter plots. Bivariate correlation analysis yielded a new positive linear correlation between the delta-HARI and the delta-MELD score (r=0.469; p<0.001). In addition, our data revealed a new negative linear correlation between delta-PVv and the delta-MELD score (r=-0.279, p=0.001). The leading cause of MICU mortality was ACLF. A subgroup analysis of patients with liver cirrhosis revealed a positive linear correlation between the delta-HARI and the delta-CLIF-C-ACLF score (r=0.252, p=0.005). Of clinical relevance, nonsurvivors of ACLF exhibited a significantly higher mean value for the delta-HARI (0.010 vs. -0.005; p=0.015) and a lower mean value for the delta-PVv (-0.7 vs. 1.9 cm/s; p=0.037) in comparison to survivors of ACLF. Conclusion: This study shows the prognostic value of the assessment of hepatic perfusion in critical care patients with severe liver diseases by bedside Doppler ultrasound examination and its utility as an accurate predictor of the outcome in patients with ACLF. Increasing HARI and a decreasing PVv are predictors of an adverse outcome. Delta-HARI and delta-PVv are new biomarkers of prognosis and ACLF-related mortality in patients with liver diseases. Delta-HARI and delta-PVv may be helpful in guiding clinical decision-making, especially in catecholamine and fluid management.